Kiprah Dakwah Virtual di Masa Pandemi Covid 19 Pada Siaran Mimbar Agama Islam di Stasiun TVRI Sumatera Utara - Wahyu Ziaulhaq (Yayasan Literasi Sains Indonesia, 2022)
This study describes the vitual da'wah during the Covid 19 pandemic on the broadcast of the Islamic religious pulpit on the TVRI station of North Sumatra. The purpose of this study is to evaluate the broadcast of the Islamic religious pulpit on TVRI North Sumatra in a structured manner. This research is a qualitative research with a descriptive approach and provides education to the reader. The data collection techniques used include observation, interviews. The results of this study are: First, Islamic broadcasting in the Islamic pulpit program at TVRI North Sumatra uses the discussion and question and answer method. Second, TVRI North Sumatra's Islamic pulpit program is effective in compiling an attractive broadcast format, presenting interactive presenters, presenting resource persons who have competence in the religious field, producing quality broadcasts, preaching materials capable of educating the audience, and providing motivational and educational shows.